2012
DOI: 10.5624/isd.2012.42.3.147
|View full text |Cite
|
Sign up to set email alerts
|

External apical root resorption in maxillary incisors in orthodontic patients: associated factors and radiographic evaluation

Abstract: PurposeThis study was performed to evaluate the incidence and degree of external apical root resorption of maxillary incisors after orthodontic treatment and to evaluate particular associated factors related to external apical root resorption.Materials and MethodsThe records and maxillary incisor periapical radiographs of 181 patients were investigated. Crown and root lengths were measured and compared on the pre- and post-treatment periapical radiographs. Crown length was measured from the center of the incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
67
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 20 publications
8
67
1
5
Order By: Relevance
“…Perkaitan antara keterukan penyerapan akar gigi pada bulan keenam dan 12 rawatan ortodontik membolehkan pengenalpastian awal terhadap risiko penyerapan akar yang lebih teruk pada seseorang individu (Artun et al 2005). Terdapat beberapa faktor berlakunya PAAL yang didorong oleh rawatan ortodontik dan ia terdiri daripada faktor variasi biologi dan faktor rawatan itu sendiri seperti morfologi akar gigi (Sameshima & Sinclair 2001), genetik (Al-Qawasmi et al 2003), sejarah trauma (Linge & Linge 1991;Nanekrungsan et al 2012), jangka masa rawatan dan magnitud daya ortodontik yang dikenakan (Fox 2005;Levander & Malmgren 1988).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Perkaitan antara keterukan penyerapan akar gigi pada bulan keenam dan 12 rawatan ortodontik membolehkan pengenalpastian awal terhadap risiko penyerapan akar yang lebih teruk pada seseorang individu (Artun et al 2005). Terdapat beberapa faktor berlakunya PAAL yang didorong oleh rawatan ortodontik dan ia terdiri daripada faktor variasi biologi dan faktor rawatan itu sendiri seperti morfologi akar gigi (Sameshima & Sinclair 2001), genetik (Al-Qawasmi et al 2003), sejarah trauma (Linge & Linge 1991;Nanekrungsan et al 2012), jangka masa rawatan dan magnitud daya ortodontik yang dikenakan (Fox 2005;Levander & Malmgren 1988).…”
Section: Pendahuluanunclassified
“…Pengaruh sejarah trauma pergigian terhadap penyerapan akar gigi semasa rawatan ortodontik telah lama dikaji (Brin et al 2003;Linge & Linge 1991, 1983Mandall et al 2006;Nanekrungsan et al 2012). Walau bagaimanapun, perbezaan teknik pengukuran antara kajian terdahulu menyebabkan kesukaran dalam membandingkan kekerapan dan keterukan PAAL.…”
Section: Perbincanganunclassified
See 1 more Smart Citation
“…Duration of treatment and horizontal (but not vertical) displacement of the incisor apices also affected proportionately root resorption, but no differences were found for slot size, archwire type, elastics, and types of expansion. 21,26 As far as biomechanical factors of orthodontic forces are concerned, human studies have shown that increased root torque, tip, and rotational movements result in greater root resorption. [29][30][31] The effects of jiggling forces on root resorption were investigated in animal studies.…”
mentioning
confidence: 99%
“…9 Both patient-related factors and orthodontic treatmentrelated factors have been reported to contribute to the degree and the severity of OIIRR. Previous investigations have linked the severity of root resorption to various factors, including type of orthodontic appliance, [10][11][12] magnitude of applied force, 2,13-16 duration of force application, [17][18][19][20][21] type of tooth movement, 2,11,12,19,22 clinical factors, 21 systemic factors, 23 patient age, [24][25][26] genetic factors related to root anomalies, 27 previous trauma, 11,12 and ethnicity. 21 Pretreatment factors were evaluated in the patients' records to help clinicians predict the incidence, location, and severity of root resorption before the orthodontic treatment.…”
mentioning
confidence: 99%